Faculty Senate, Minutes, October 18, 2012 - Faculty Senate, Valdosta State University (Valdosta, Ga.: Valdosta State University Archives and Special Collections)
Faculty Senate, Meeting Minutes for October 18, 2012. Tracy Woodard-Meyers, President; Ed Walker, Vice President/President Elect; Diane Holliman, Secretary; Aubrey Fowler, Parliamentarian;
1 electronic record. Faculty Senate Meeting Minutes for October 18, 2012. 18 pages.
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Committees; Electronic records